IDDF2022-ABS-0085 Inhibition of colorectal cancer by scutellarin via modulation of hippo signaling pathway activity. (2nd September 2022) - Yang, Han; Liu, Maolun; Ren, Shan; Zhao, Hui; Ming, Tianqi; Tang, Shun; Tao, Qiu; Xu, Haibo
Abstract : Background: It has become a widely held view that dysregulation of the Hippo signaling pathway is involved in the occurrence and development of various types of cancers, including colorectal cancer (CRC). Scutellarin, a type of phytochemical flavonoid abundant in Scutellaria Barbata, possesses powerful efficacies on many afflictions, particularly CRC, with the underlying mechanisms to be elucidated. In the present study, the pharmacological effects of scutellarin on CRC were investigated, with a focus on the influence of scutellarin on the Hippo signaling pathway. Methods: In HCT116 CRC cells, the effects of scutellarin on the proliferation, migration, colony formation, apoptosis and cell cycle were detected, with measurement of Hippo signaling pathway activity. Using the mouse model of subcutaneous HCT116 xenograft tumor, the effectiveness of scutellarin on the pathogenesis, apoptosis and Hippo signaling axis in CRC tissues was also probed as well. Results: Scutellarin retarded the proliferation, migration and colony formation of HCT116 cells in a concentration-dependent mode. Flow cytometric analysis and Hoechst 33342/PI staining discovered that scutellarin caused apoptosis of HCT116 cells and arrested cell cycle at G/G1 phase, with decreased expression of anti-apoptotic BCL-2 (B-cell lymphoma 2), and increased level of pro-apoptotic BAX (BCL-2-associated X), caspase-9 and caspase-3. Additionally, scutellarin markedly promoted the expressions of MST1 (mammalian sterile 20-like kinases 1) and LATS1 (large tumor suppressor 1), and diminished the levels of YAP1 (yes-associated protein 1), TAZ (transcriptional co-activator with PDZ-binding motif), c-Myc and cyclin D1 in HCT116 cells. In HCT116 xenograft tumor assay, scutellarin heavily impeded tumor growth and alleviated pathological features. The induction of apoptosis in CRC tissues by scutellarin was validated by TUNEL assay, accompanied by lower BCL-2 expression and higher levels of BAX, caspase-9 and caspase-3, versus the control. Moreover, scutellarin substantially augmented the expressions of MST1 and LATS1, and mitigated the levels of YAP1, TAZ, c-Myc and cyclin D1 in CRC tissues, as revealed by the analyses of qRT-PCR, western blot and immunohistochemistry. Conclusions: In summary, scutellarin may exert the efficacy against CRC, potentially by modulation of Hippo signaling pathway activity.